2005
DOI: 10.4141/s04-005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting nitrogen fertilizer requirements for corn by chlorophyll meter under different N availability conditions

Abstract: Rashid, M. T., Voroney, P. and Parkin, G. 2005. Predicting nitrogen fertilizer requirements for corn by chlorophyll meter under different N availability conditions. Can. J. Soil Sci. 85: 149-159. Nitrogen management strategies that enhance fertilizer use efficiency and maximize profitability in corn require a rapid and accurate method to determine the crop N needs of current hybrids. The objective of this study was to evaluate the potential of a portable chlorophyll meter for predicting N fertilizer requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
6
20
0
1
Order By: Relevance
“…Precipitations at St. Louis in 2004 and at Ste. Catherine in 2006 were similar but corn hybrids and site characteristics were different (Table 1); these factors could have affected CM readings (Blackmer and Schepers, 1994; Waskom et al, 1996; Sunderman et al, 1997; Bullock and Anderson, 1998; Costa et al, 2001; Rashid et al, 2005; Hawkins et al, 2007). Other factors that can reportedly affect CM readings include: developmental stage (Argenta et al, 2004; Scharf et al, 2006; Hawkins et al, 2007), disease or insect damage (Piekielek et al, 1995; Junqueira et al, 2004), plant density (Hashemi‐Dezfouli and Herbert, 1992; Blackmer et al, 1993), and other nutrient deficiencies (Masoni et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Precipitations at St. Louis in 2004 and at Ste. Catherine in 2006 were similar but corn hybrids and site characteristics were different (Table 1); these factors could have affected CM readings (Blackmer and Schepers, 1994; Waskom et al, 1996; Sunderman et al, 1997; Bullock and Anderson, 1998; Costa et al, 2001; Rashid et al, 2005; Hawkins et al, 2007). Other factors that can reportedly affect CM readings include: developmental stage (Argenta et al, 2004; Scharf et al, 2006; Hawkins et al, 2007), disease or insect damage (Piekielek et al, 1995; Junqueira et al, 2004), plant density (Hashemi‐Dezfouli and Herbert, 1992; Blackmer et al, 1993), and other nutrient deficiencies (Masoni et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Chlorophyll meter readings have proven effective as a rapid diagnostic method to determine the N status of many crops, including spring wheat ( Triticum aestivum L.) (Follett et al, 1992; Vidal et al, 1999; Arregui et al, 2006), rice ( Oryza sativa L.) (Turner and Jund, 1991; Peng et al, 1993; Ladha et al, 1998), potato ( Solanum tuberosum L.) (Minotti et al, 1994), and corn (Piekielek and Fox, 1992; Schepers et al, 1992; Dwyer et al, 1995). Critical values or ranges of CM readings have been defined to maximize corn yields in Canada (Zebarth et al, 2002; Rashid et al, 2005), the United States (Piekielek and Fox, 1992; Waskom et al, 1996; Sunderman et al, 1997), and Brazil (Argenta et al, 2004). These values are usually based on the relationship between CM readings and relative corn grain yield (RY) (Piekielek and Fox, 1992; Blackmer and Schepers, 1994; Fox et al, 2001; Argenta et al, 2004; Rashid et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of relative SPAD as a N nutrition diagnosis index was not affected by the cultivar, and the correlation coefficients for the relative SPAD vs. the relative yield were greater than SPAD vs. yield (Hawkins et al 2007, Ziadi et al 2008. It was concluded that the SPAD meter was more useful as a diagnostic aid, rather than a N-management tool for corn (Rashid et al 2005).…”
Section: Correlation Between Spad Readings and Corn Grain Yieldmentioning
confidence: 95%
“…Overall, both FIT and 75% FIT had NNI close to 1.0 from 83 DAP in both year, the 60% FIT, 50% FIT and the rainfed treatments sowed NNI values less than 1 from about 108 DAP toward the end of the growing season. Critical nutrient concentrations separate nutrient deficiency from nutrient sufficiency, but they vary with plant parts, physiological age, and environmental factors (Munson and Nelson, 1990;Westfall et al, 1990;Herrmann and Taube, 2004;Rashid et al, 2005). The onset of N deficiency occurred in mid-August (108 DAP) under limited irrigation and rainfed treatments when the crops reached the grain-filling stage (Figure 4).…”
Section: N O N -C O M M E R C I a L U S E O N L Ymentioning
confidence: 99%